On the reliability of system under non-instanteneous time of renewal - Sapagovas, J. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: И. Сапаговас. О надежности системы при немгновенном времени восстановления J. Sapagovas. Apie sistemos patikimumą, esant nenuliniam atstatymo laikui